2022
DOI: 10.1111/eva.13427
|View full text |Cite
|
Sign up to set email alerts
|

An allozyme polymorphism is associated with a large chromosomal inversion in the marine snail Littorina fabalis

Abstract: For many decades, a central question in population genetics has been to understand how divergent natural selection promoting local adaptation interacts with other microevolutionary processes to shape genetic differences among populations. Early suggestions of candidate genes involved in local adaptation were described at allozyme loci

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 86 publications
1
8
0
Order By: Relevance
“…saxatilis (Westram et al, 2018 ) and the closely related L . fabalis (see Le Moan, et al, 2022 ). At the same time, other barriers, such as assortative mating and intrinsic genetic incompatibilities seem to play minor roles (Johannesson et al, 2020 ; Perini et al, 2020 ).…”
Section: Cemeb Scientific Highlightsmentioning
confidence: 98%
“…saxatilis (Westram et al, 2018 ) and the closely related L . fabalis (see Le Moan, et al, 2022 ). At the same time, other barriers, such as assortative mating and intrinsic genetic incompatibilities seem to play minor roles (Johannesson et al, 2020 ; Perini et al, 2020 ).…”
Section: Cemeb Scientific Highlightsmentioning
confidence: 98%
“…Early genetic work found sharp allele frequency differences at the arginine kinase locus ( Ak ) along the environmental cline between these ecotypes (Tatarenkov & Johannesson, 1994 , 1998 ). Using whole‐genome sequencing, Le Moan et al ( 2022 ) revisited this historically studied system to increase our understanding of the Ak variation and its relationship to the divergence between the two ecotypes. Le Moan et al ( 2022 ) not only found nine nonsynonymous substitutions, which were a perfect fit to the different migration patterns of the Ak alleles, but also discovered that the Ak alleles were located on different arrangements of a putative chromosomal inversion.…”
Section: Overview Of the Issuementioning
confidence: 99%
“…One major topic studied within the Marine Evolutionary Biology community is the interplay between genetic and plastic mechanisms in the processes of local adaptation, ecotype formation, and speciation, and how these processes may be impacted by, e.g., sexual selection, individuals' dispersal patterns, or species‐specific genomic properties, such as the size and distribution of chromosomal rearrangements (e.g., Faria et al, 2021 ; Ravinet et al, 2017 ). Herein, these processes are addressed in diverse empirical model systems ranging from diatoms to mollusks and fish (Green et al, 2022 ; Le Moan et al, 2022 ; Sefbom et al, 2022 ; Zhang et al, 2022 ), as well as in silico in two theoretical modeling studies (Eriksson et al, 2022 ; Marshall & Connallon, 2022 ). The link between genotype and phenotype is also the focus of several empirical studies here (Gefaell et al, 2022 ; Stenger et al, 2022 ; Walker et al, 2022 ), as is the seascape genomics of a wide range of taxa (Delaval, Bendall, et al, 2022 ; Delaval, Frost, et al, 2022 ; Fitz et al, 2022 ; Lapègue et al, 2022 ; Matias et al, 2022 ; Palumbi et al, 2022 ; Pampoulie et al, 2022 ), which has important implications for management of marine resources.…”
Section: Introductionmentioning
confidence: 99%
“…Marine snails of the genus Littorina are emerging models for studying the role of chromosomal inversions in speciation 21,23,24 . Littorina includes several species that form ecotypes that differ in multiple phenotypic traits (including shell size, shell morphology, and behaviour).…”
Section: Introductionmentioning
confidence: 99%